PELABUHAN WINI NUSA TENGGARA TIMUR DARI MASA KE MASA: STUDI ETNOARKEOLOGI - Wachid Azis; Widya Nayati (Forum Arkeologi, 2014)
Trading in Timor island was estimated to happened since 16th century. The foreign traders came to Timor island to seek sandalwood, honey, and beeswax to be traded again in their homeland. The purpose of this research is determining activities and role of trading, as well as the Kingdom of Bibokis role in Port Wini. This is a qualitative research. Data were collected through literature study, observation, and interview with ethnoarchaeological method. The data were analyzed by inductive approach and descriptively presented. Port Wini is located in a strategic position and became one of trading centre in the past and still developing until now. In the kingdom era, the king took the role as controler of the port and monopolized sandalwood trading with foreign traders.Perdagangan di Pulau Timor diperkirakan sudah berlangsung sejak abad ke-16 Masehi. Para pedagang asing datang ke Pulau Timor untuk mencari cendana, madu, dan lilin untuk diperdagangkan kembali di daerah asal mereka. Tujuan penelitian ini adalah untuk mengetahui peranan dan aktivitas perdagangan serta peran Kerajaan Biboki di Pelabuhan Wini. Penelitian ini bersifat kualitatif. Data didapat melalui studi pustaka, observasi, dan wawancara dengan pendekatan etnoarkeologi. Data dianalisis secara induktif dan disajikan secara deskriptif. Lokasi Pelabuhan Wini sangat strategis dan menjadi salah satu pusat perdagangan sejak dahulu dan terus dikembangkan hingga sekarang. Pada jaman kerajaan, raja sebagai pemegang kontrol atas pelabuhan ini memonopoli perdagangan cendana dengan asing.